KOMUNIKASI PEMASARAN MODEL AISAS (Attention, Interest, Search, Action, Share) DALAM STRATEGI MEMBANGUN REPUTASI BRAND DAILYHOTELS.ID (Universitas Negeri Surabaya, 2023)
His research discusses Dailyhotels.id as a media service to increase partner hotel promotion. Through the media and creative content created, it helps partner hotels excel and stand out among the many existing hotels. Researchers use one of the marketing formulas that are trending in the digital age, namely the AISAS model. This study aims to determine whether the strategies used by Dailyhotels.id in building brand reputation also include the AISAS model (attention, interest, search, action, share). This research uses a qualitative approach and data collection techniques in this study using structured interviews with Dailyhotels.id business actors, namely Founder, marcomm, social media team and marcomm hotel partners. The results of the study were tested using the triangulation technique and tested qualitatively. The results of this study indicate that the use of social media and websites by paying attention to every detail of the content or information uploaded has a significant impact on business partners and the audience. Dailyhotels.id has implemented the AISAS model at each stage as a strategy to build brand reputation. However, the author found that this AISAS model is very flexible because business partners do not always follow the five steps in this order.